2020
DOI: 10.3233/jad-191227
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid, Tau, and Neurodegeneration (A/T/N) Classification Applied to a Clinical Research Cohort with Long-Term Follow-Up

Abstract: Background: The unbiased amyloid, tau, and neurodegeneration (A/T/N) classification is designed to characterize individuals in the Alzheimer continuum and is currently little explored in clinical cohorts. Objective: A retrospective comparison of the A/T/N classification system with the results of a two-year clinical study, with extended follow-up up to 10 years after inclusion. Methods: Patients (n = 102) clinically diagnosed as Alzheimer's disease (AD) with dementia or amnestic mild cognitive impairment (MCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…As the ratio of Aβ42 to T-tau can be artificially increased via increases in T-tau levels only, however, (e.g., due acute brain disorders such as trauma or stroke) it has been recommended that CSF AD biomarkers are to be interpreted as independent measures [ 9 ]. When applying the Aβ (A), tau (T) and neurodegeneration (N) (A/T/N) classification system using CSF AD biomarkers to extended follow-up data (up to 10 years), while the highest proportion of progression from MCI to AD dementia was seen in patients who were A+T+N+, progression was also common in patients showing A-T+N+ and A-T-N- [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the ratio of Aβ42 to T-tau can be artificially increased via increases in T-tau levels only, however, (e.g., due acute brain disorders such as trauma or stroke) it has been recommended that CSF AD biomarkers are to be interpreted as independent measures [ 9 ]. When applying the Aβ (A), tau (T) and neurodegeneration (N) (A/T/N) classification system using CSF AD biomarkers to extended follow-up data (up to 10 years), while the highest proportion of progression from MCI to AD dementia was seen in patients who were A+T+N+, progression was also common in patients showing A-T+N+ and A-T-N- [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inspections revealed that only two patients had the A‐T‐N+ profile, one of whom received the diagnosis of hippocampal sclerosis probably due to TDP43 proteinopathy and the other was inconclusive. However, other authors 83 recently reported that some individuals with amnestic MCI progressed to clinical AD dementia within all four major A/T/N groups including A‐T + N+ and A‐T‐N‐. They suggested that when selecting individuals for research, a combination of the A/T/N framework and clinical status may be necessary because the prognostic value of the former depends on the latter.…”
Section: Knowledge Creationmentioning
confidence: 99%
“…An interesting single case was recently published that sheds new light on the causal mechanisms of AD dementia and the A/T/N framework. 84…”
Section: Cost Of Biomarkers (Prioritymentioning
confidence: 99%
“…SNAP does not represent preclinical AD, but includes one or more neuropathological processes or diseases other than AD [37]. SNAP is common in both clinically asymptomatic and cognitively impaired individuals [38,39]. In our study, the presence of SNAP was relatively consistent across different clinical groups (HC24.5%, MCI 22.3%, and AD 21.1%).…”
Section: Discussionmentioning
confidence: 48%